Pembuatan Aplikasi Absensi Berbasis Flutter untuk Meningkatkan Efisiensi Monitoring Kehadiran - Fransiska Harahap; Richi Andrianto; Intan Maimunah; Muhammad Gusti Fhaturrahman Daulay; Muhammad Husein; Muhammad Sampurna; Patimah Harahap (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This journal discusses the creation of a Flutter-based attendance application that aims to increase efficiency in monitoring attendance on campus. The presence of students in each lecture session has an important role in the learning process and academic management. However, traditional attendance systems are often prone to errors, difficult to track data, and less efficient in gathering information. In this study, the authors designed and developed an attendance application using the Flutter framework, which allows applications to run cross-platform (multi- platform). This application is designed to make it easier for students and lecturers in the process of recording attendance with features such as using QR codes, face identification, or manual options. In addition, this application is also equipped with an administrative dashboard for lecturers and staff to monitor student attendance in real- time. The development method includes designing an intuitive and responsive user interface, implementing a data security system, and integrating with the campus database system. The results of application testing show increased efficiency in attendance monitoring, reduction of recording errors, and easy access to digital attendance data. It is hoped that this application can make a positive contribution in managing attendance on campus and encourage the application of modern technology in the academic process.